The Effectiveness of Role-Playing Games (RPG) in Teaching Reading for Second Grade Students at Man 2 Lombok Tengah - Juniardi, Juniardi; Khusniyah, Nurul Lailatul; Ariawan, Soni (EDUJ : English Education Journal, 2023)
The research entitled the effectiveness of Role Playing Game (RPG) examined in this research was how the effect of using Role playing game (RPG) to increase the second grade students reading comprehension at MAN 2 Lombok Tengah. This research was aimed to find out whether the use of Role-Playing Game (RPG) was effective or not to increase the second-grade students’ reading comprehension at MAN 2 Lombok Tengah. This research uses quantitative research methods with a pre-experimental approach in one group pre test and post test. This research was conducted at MAN 2 Lombok Tengah which consist of 112 second grade students in total and Class XI IBB was chosen as a sample with total of 17 students. The instruments used were a test of narrative that consist of 20 multiple choices. The research findings showed that the students’ difference before and after using Role Playing Game (RPG) was significantly effective. The results showed that students' pre-test scores were smaller than post test with mean score of pre test was 60.59. While the scores of post-test after treatment got better score than pre test, with mean score of 77.6. After that, 2 paired sample T-test was applied with a significance value of sig. (2 paired) was 0.001. Because the results obtained are Sig < a or 0.001 < 0.05. Then H0 is rejected and Ha is accepted. Therefore, based of the findings it can be concluded that the use of Role Playing Games (RPG) is effective to increase students' reading comprehension.